Perceived Organizational Support and Teachers' Work Engagement: The Mediating Role of Work Motivation in Indramayu Regency: Penelitian - Raditia Lin (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the influence of the perception of organizational support on teachers' work involvement with work motivation as a mediating variable in teachers in Indramayu Regency. The background of this research is based on the phenomenon of low motivation and work involvement of teachers, even though the role of teachers greatly determines the quality of education. The research method used is quantitative with a survey design. The study respondents totaled 230 teachers from various levels of education who were selected using the proportional stratified random sampling technique. The research instrument was in the form of a questionnaire with a Likert scale to measure three main constructs, namely perception of organizational support, work motivation, and teacher work involvement. Data analysis was carried out with Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS. The results of the study showed that the perception of organizational support had a positive and significant effect on teacher work involvement. Organizational support also has a positive effect on work motivation, and work motivation has been shown to have a significant effect on work engagement. Furthermore, mediation analysis found that work motivation plays a partial mediator in the relationship between perceptions of organizational support and work engagement. The implications of this study emphasize the importance of schools and education offices to improve organizational support practices through recognition of achievements, effective communication, and the provision of professional development programs. Further research suggests adding other variables such as job satisfaction or leadership style, as well as using longitudinal design to provide a more comprehensive picture of teachers' motivation dynamics and work engagement.